2013
DOI: 10.3389/fimmu.2013.00242
|View full text |Cite
|
Sign up to set email alerts
|

NLRP7 and the Genetics of Hydatidiform Moles: Recent Advances and New Challenges

Abstract: NOD-like receptor proteins (NLRPs) are emerging key players in several inflammatory pathways in Mammals. The first identified gene coding for a protein from this family is Nlrp5 and was originally called Mater for “Maternal Antigen That Mouse Embryos Require” for normal development beyond the two-cell stage. This important discovery was followed by the identification of other NLRPs playing roles in inflammatory disorders and of the first maternal-effect gene in humans, NLRP7, which is responsible for an aberra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 110 publications
1
41
0
2
Order By: Relevance
“…Interestingly, the expression of some NLR family members, including NLRP2, -3 and -10, was previously detected at high levels in reproductive organs [48]. Indeed, mutations in the NLR gene NLRP7 has been described as a causative hallmark for recurrent hydatidiform moles (RHM) and reproductive loss [49]. …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression of some NLR family members, including NLRP2, -3 and -10, was previously detected at high levels in reproductive organs [48]. Indeed, mutations in the NLR gene NLRP7 has been described as a causative hallmark for recurrent hydatidiform moles (RHM) and reproductive loss [49]. …”
Section: Discussionmentioning
confidence: 99%
“…8 In rare cases the PHM have also been reported with other karyotypes (diploid biparental, triploid dyginic, tetraploid triandric). 52 These explanations were reconsidered in 2003 by Golubovsky 53 . He points out that (1) it would need a regular "stock" of anuclear oocytes in order to ensure the frequency of the CHM, (2) the empty oocytes can be obtained "in vitro" but question their viability "in vivo" and/or whether they can be fertilized (3) in the case of twins, of which one is a CHM and the other a fetus, it has been observed that the prevalence of CHM diploids is androgenetic 46XX, 54 which can be explain by diploidization concept and the monozygotic origin of such associations (Fig.…”
Section: Genetic Backgroundmentioning
confidence: 99%
“…En fait, de nombreuses combinaisons chromosomiques ont pu être observées. La présence de deux populations cellulaires de caryotype différent a également été rapportée, on parle alors de môle complète mosaïque [13]. Retenons que dans la majorité des cas, ces môles complètes sont d'origine androgénétique.…”
Section: Fréquenceunclassified
“…Par exemple, l'ovocyte est anucléé avant ou décennies, ces fréquences ont tendance à baisser [13]. La surveillance médicale et la meilleure nutrition de la mère expliquent la diminution de ces pathologies qui restent, dans 80 % des cas, des tumeurs bénignes dans les pays développés.…”
Section: Les Hypothèses Explicatives Hypothèses Historiquesunclassified